Membangun Dan Memajukan Bisnis Di Indonesia Dengan Inward-Outward Looking - R. Gatot Heru Pranjoto (Jurnal Studi Manajemen dan Bisnis, 2014)
The success of a country begins with success in economic development, through the development of industry and business. Industrial and business success is achieved when the national movement for change and build, starting from the government in the running community development programs as well as the level of awareness and high transparency. Government and society must be open and willing to be evaluated based on the results of his efforts on the development of government programs with regard to the potential of each region.The construction process is very important, starting with the development of human resources, and natural resources in Indonesia, has been very abundant natural resources, but is not followed by the optimization of production, lack of professional actors and state officials (Executive, Legislative, Yudukatif) and businesses, for it must be created by a national program how to generate leadership (leadership) nationwide, as well as how to form a community of professional business people in Indonesia and smart, with the hope of future industrial forming a superior, independent, able to compete in the global market and is able to be host in the land itself.